2020
DOI: 10.1186/s12906-020-03019-x
|View full text |Cite
|
Sign up to set email alerts
|

The possibilities and challenges of integrative medicine implementation in clinical psychology: a qualitative study in Indonesia

Abstract: Background Integrative medicine (IM), which is the integration of complementary and alternative medicine (CAM) into conventional health services, has been applied in some nations. Despite its highly relevant holistic approach with the improvement of mental health care using person-centred approach, there are limited studies that discuss IM, specifically in clinical psychology. Therefore, this qualitative study aimed to explore the perspectives of Indonesian clinical psychologists (CPs) on the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Similarly, Barimah and Akotia [ 18 ] observed that “Despite this growth in consumer demands for complementary medicine or TRM [traditional medicine], the policy responses of African and other governments and health professions have been either absent or inadequate” ([ 18 ] p. 100). The discipline of psychology may not be adequately informing psychologists on how they might engage with their client’s preference for CM as part of mental health treatment [ 3 , 19 ]. In the context of informed consent, Liem’s research on psychologists in Indonesia and Australia [ 2 ] reported that participants believed “clients have the right to know all the possible treatments available, including CAM [CM] treatments, and their safety and effectiveness” (p. 6).…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Barimah and Akotia [ 18 ] observed that “Despite this growth in consumer demands for complementary medicine or TRM [traditional medicine], the policy responses of African and other governments and health professions have been either absent or inadequate” ([ 18 ] p. 100). The discipline of psychology may not be adequately informing psychologists on how they might engage with their client’s preference for CM as part of mental health treatment [ 3 , 19 ]. In the context of informed consent, Liem’s research on psychologists in Indonesia and Australia [ 2 ] reported that participants believed “clients have the right to know all the possible treatments available, including CAM [CM] treatments, and their safety and effectiveness” (p. 6).…”
Section: Key Pointsmentioning
confidence: 99%
“…Some psychologists report engaging with CM based on holistic and client centred principles [ 3 , 35 , 36 ], while others discuss client demand and acknowledge the cultural relevance of some CM (Barimah and Akotia 2015 [ 18 , 37 39 ]. Psychologists are also seeking training in, and already using, some CM approaches in their practice [ 1 , 3 , 4 , 19 ]. Prevalence rates for psychologists integrating CM into their practice vary dependent on research aims, methodologies, and what is included in definitions of CM.…”
Section: Key Pointsmentioning
confidence: 99%
“…Previously, before the occurrence of COVID-19, many works have presented that an integrated medicinal approach could give better results not only on the physical ailments but also the mental and social aspects of an individual in many diseases [13][14][15]. Many researchers argue that integrated medicine could be the future of medicine to take care of all the ailments of human health and thus could significantly improve the quality of life [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that an integrated medicine strategy can improve outcomes not just for physical illnesses but also for mental and social dimensions of an individual in many diseases 11–13 . Many scholars believe that integrated medicine is the future of medicine since it can address all dimensions of human health problems and enhance people's quality of life and disease prognosis 14–16 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that an integrated medicine strategy can improve outcomes not just for physical illnesses but also for mental and social dimensions of an individual in many diseases. [11][12][13] Many scholars believe that integrated medicine is the future of medicine since it can address all dimensions of human health problems and enhance people's quality of life and disease prognosis. [14][15][16] However, little emphasis has been paid to evaluating and assessing both eastern (traditional Chinese medicine, yoga, naturopathy, and Ayurveda) and western therapies, that is, integrated medicine, in managing SARS-CoV-2 patients in all dimensions of health, including physical, mental, and social.…”
Section: Discussionmentioning
confidence: 99%